Proteomic analysis of C2C12 myoblast and myotube exosome-like vesicles: a new paradigm for myoblast-myotube cross talk? - Alexis Forterre (Public Library of Science (PLoS), 2014)
Exosomes are nanometer-sized microvesicles formed in multivesicular bodies (MVBs) during endosome maturation. Exosomes are released from cells into the microenvironment following fusion of MVBs with the plasma membrane. During the last decade, skeletal muscle-secreted proteins have been identified with important roles in intercellular communications. To investigate whether muscle-derived exosomes participate in this molecular dialog, we determined and compared the protein contents of the exosome-like vesicles (ELVs) released from C2C12 murine myoblasts during proliferation (ELV-MB), and after differentiation into myotubes (ELV-MT). Using a proteomic approach combined with electron microscopy, western-blot and bioinformatic analyses, we compared the protein repertoires within ELV-MB and ELV-MT. We found that these vesicles displayed the classical properties of exosomes isolated from other cell types containing components of the ESCRT machinery of the MVBs, as well as numerous tetraspanins. Specific muscle proteins were also identified confirming that ELV composition also reflects their muscle origin. Furthermore quantitative analysis revealed stage-preferred expression of 31 and 78 proteins in ELV-MB and ELV-MT respectively. We found that myotube-secreted ELVs, but not ELV-MB, reduced myoblast proliferation and induced differentiation, through, respectively, the down-regulation of Cyclin D1 and the up-regulation of myogenin. We also present evidence that proteins from ELV-MT can be incorporated into myoblasts by using the GFP protein as cargo within ELV-MT. Taken together, our data provide a useful database of proteins from C2C12-released ELVs throughout myogenesis and reveals the importance of exosome-like vesicles in skeletal muscle biology.